Assessment of Nursing College Students' Health Protective Behaviors - Kudhair, talib (Iraqi National Journal of Nursing Specialties, 2007)
Objective: to assess the Nursing College students' health-protective behaviors (HPBs) and theirassociation with some sociodemograghic characteristics.Methodology: A sample of 100 Students (males and females) was selected through a systematicrandom sample that were at the third and fourth year of Nursing College in Baghdad University for theperiod of April 1st through April 30th 2007. Data were collected through the use of a self-reportinstrument that used for Americans as HPBs assessment that contains 23 items. Reliability and validityof the tool were determined through a pilot study. A descriptive statistical approach (frequencies andpercentages) and inferential statistical approach (chi-square) were used for data analysis.Results: the study indicated that health protective behaviors (HPBs) of the students were bad and thereis a significant relationship between HPBs of the students and their sociodemograghic characteristics.Recommendations: the study recommended that an education program can be designed, conducted,and implemented to the universities' students as well as further and nation-wide studies can be on alarge sample size of colleges of nursing students.